2018
DOI: 10.1021/acs.organomet.8b00474
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Catalyst Generation and Benchtop-Compatible Entry Points for TiII/TiIV Redox Catalytic Reactions

Abstract: The development of several in situ generated catalyst systems for Ti-catalyzed oxidative nitrene transfer reactions is reported. The simplest and widely applicable catalyst system, TiCl 4 (THF) 2 / Zn 0 , can be set up on the benchtop under air. This system uses commercially available reagents and can be used as an entry point for Ti II /Ti IV multicomponent redox reactions for the synthesis of pyrroles, α,γ-unsaturated imines, α,β-unsaturated imines, cyclopropylimines, and arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…This scope demonstrates that multisubstituted pyrazoles can be accessed directly and generally in a single step through multicomponent coupling of Ti imidos, while avoiding prerequisite hydrazine or hydrazine-derived coupling partners. Conveniently, [py 2 TiCl 2 (NPh)] 2 and derivatives thereof can be prepared in a single pot from TiCl 4 (THF) 2 , and we have recently demonstrated benchtop-compatible Ti imido generation . Thus, access to these multicomponent coupling reactions does not require specialized equipment or protocols.…”
Section: Resultsmentioning
confidence: 95%
“…This scope demonstrates that multisubstituted pyrazoles can be accessed directly and generally in a single step through multicomponent coupling of Ti imidos, while avoiding prerequisite hydrazine or hydrazine-derived coupling partners. Conveniently, [py 2 TiCl 2 (NPh)] 2 and derivatives thereof can be prepared in a single pot from TiCl 4 (THF) 2 , and we have recently demonstrated benchtop-compatible Ti imido generation . Thus, access to these multicomponent coupling reactions does not require specialized equipment or protocols.…”
Section: Resultsmentioning
confidence: 95%
“…We have previously shown that this strategy is a benchtop-compatible approach to other Ti oxidative amination reactions. 54 This one-pot approach facilitates the in situ formation of diazatitanacycle intermediates such as 1 without the need for specialized equipment, making the synthesis of both α-diimines and pyrazoles 32 more operationally simple.…”
Section: Resultsmentioning
confidence: 99%
“…3), such as CAT3. The proposed catalytic cycle for this process, determined through combined experimental and computational studies, [35][36][37][38] is highlighted in Fig. 3.…”
Section: Pyrroles Furans and Thiophenesmentioning
confidence: 99%